Exploring the Drivers of Employee Creativity in Chengdu’s State-Owned Creative Enterprises in Chengdu, China - Liu, Qiaochen (Scholar: Human Sciences, 2025)
Purpose: This article aims to investigate the key factors that affect the development of employee creativity in state-owned creative companies in Chengdu, Sichuan, China. The conceptual framework proposes a causal relationship research design, data, and methods between Coworker Support, Leadership Support, Procedural Justice, Intrinsic Motivation, Intelligent Stimulation, Individualized Consideration, and Employee Creativity. Research design, data, and methodology: The researchers used quantitative methods (n=500) to distribute questionnaires to employees of state-owned creative companies. The study used quantitative methods to collect data from the target population through questionnaire surveys. Describe the process of data collection and statistical processing. Structural Equation Model (SEM) and Confirmatory Factor Analysis (CFA) are used for data analysis, including model fitting, structural reliability, and effectiveness. Result: The research findings indicate that coworker support, leadership support, procedural justice, intrinsic motivation, intelligent stimulation, and individualized consideration have a significant impact on employee creativity. Individualized consideration has the greatest impact on employee creativity, followed by intrinsic motivation, intelligent stimulation, procedural justice, leadership support, creative role identity, and coworker support. Conclusion: Seven hypotheses have been proven to meet the research objectives. Therefore, it is recommended that the company’s management and human resources team provide evaluations, prioritize the development of employee creativity, and develop corresponding implementation plans to enhance employee creativity.